Editorial: low population mortality from COVID‐19 in countries south of latitude 35 degrees North supports vitamin D as a factor determining severity. Issue 12 (28th April 2020) - Rhodes, Jonathan M.; Subramanian, Sreedhar; Laird, Eamon; Kenny, Rose A.
Abstract : LINKED CONTENT This article is linked to Al‐Ani et al and Garg et al papers. To view these articles, visit https://doi.org/10.1111/apt.15779 and https://doi.org/10.1111/apt.15796 .